INTENSITAS KERJA AKTIVITAS NELAYAN PADA PENGOPERASIAN SOMA PAJEKO (MINI PURSE SEINE) DI BITUNG - Handayani, Suci n; Wisudo, Sugeng H; Iskandar, Budhi H; Haluan, John (Jurnal Teknologi Perikanan dan Kelautan, 2015)
There are factors of accident at sea in fishing activities which 80% caused by human errors (FAO 2009). The number of fishing vessel accidents within 7 years (January 2007-November 2013) in PPS Bitung occurred 40 times and tends to increase. There were accidents of six types of fishing vessels which majority soma pajeko (mini purse seine) that not recorded within 2010-2013 in Bitung. It is necessary to study fishermen safety on soma pajeko fishing operations because the number of fishermen is quite a lot. The research objectives are to identify and determine the work intensity of fishermen activity in soma pajeko operation which potentially cause work accident at sea. This research method is a numerical descriptive. Data were analyzed by identifying activities with Hierarchical Task Analysis (HTA). Study result shows that stages of soma pajeko activities at PPS Bitung sorted into 8 phases with total 58 activities. Number of crew on soma pajeko fishing vessel examined as 28 persons with the greatest portion of responsibility burdens is Captain. Total work intensity to perform all activities (beginning to end) on soma pajeko operation requires crew involvement/ power forces equivalent to 563 OA (men activity). The greatest primary work intensity is on the 5th stage (bauling) which showed the biggest activity level with primary work intensity index of 0.29. Involvement crew on bauling was the biggest intensity (139 OA) which potentially occurs the risk possibility of work accidents caused by human error that bigger than other activities.